2011
DOI: 10.1111/j.1755-053x.2011.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of the Stated Purposes of Issuer Tender Offers to Purchase Common Stock

Abstract: This paper documents the purposes of issuer tender offers to repurchase stock, as stated in Securities and Exchange Commission (SEC) disclosures, over the period 1994‐2006. We explore whether stated purposes relate to announcement period returns and find returns are significantly lower when repurchases replace dividends, distribute cash from unspecified sources, or occur subsequent to third‐party tender offers. Announcement period returns are significantly higher when repurchases are viewed by management as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
(188 reference statements)
0
4
0
Order By: Relevance
“…Beyond signaling, there are other explanations for repurchases and some studies find support for them. Grullon and Michaely (2004) and Dunn et al (2011) empirically support Jensen's (1986) agency cost of free cash flow theory. Repurchasing of shares can also be a means of transferring cash to shareholders and may be useful for tax efficiency reasons instead of dividends (see Bierman and West, 1966, Moser, 2007, and Hsieh and Wang, 2008.…”
Section: Empirical Literaturementioning
confidence: 67%
See 1 more Smart Citation
“…Beyond signaling, there are other explanations for repurchases and some studies find support for them. Grullon and Michaely (2004) and Dunn et al (2011) empirically support Jensen's (1986) agency cost of free cash flow theory. Repurchasing of shares can also be a means of transferring cash to shareholders and may be useful for tax efficiency reasons instead of dividends (see Bierman and West, 1966, Moser, 2007, and Hsieh and Wang, 2008.…”
Section: Empirical Literaturementioning
confidence: 67%
“…Repurchasing stock can be the best investment opportunity of the firm (see D 'Mello and Shroff, 2000). Dunn et al (2011) document that returns are highest to repurchase announcements when a company's management consider repurchases as their best investment opportunity (as stated in their SEC filings).…”
Section: Empirical Literaturementioning
confidence: 99%
“…When analysed in this vein, it was observed that some of the studies in the list examined the "cash flow theory" in finance but were included in the review pool as it included the statement of flow theory (e.g. Dunn et al, 2011;Eldomiaty & Ismail, 2009;Smith & Pennathur, 2019); some of them were related to the topics of informatics (Li, Ji, Gan, Qu & Ran, 2021;Wani, Raghavan, Abraham & Kleist, 2017) or mechanics (Ozdemir, Souli, & Fahjan, 2010); and some of them only mentioned flow theory within the text but did not use it as the main or one of the main theories of the study (e.g. Huang et al, 2019;Rodrigues et al, 2016;Tran & Chang, 2022).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…According to the signaling hypothesis, repurchase firms use the announcement of OMR's signal to convey the information of firm stock undervaluation to affect stock return on the market (Jagannathan & Stephens, 2003;Zhang, 2005;Dunn, Fayman, & McNutt, 2011;Huang, 2015). Li (2016) found that the positive abnormal returns incurred after the announcement of Taiwan's share repurchase have the first-month effect because it is the result of receiving the firm information.…”
Section: Literature Reviewmentioning
confidence: 99%